Potential uses of silkworm pupae (Bombyx mori L.) in food, feed, and other industries: a systematic review - Rodríguez-Ortiz, Luis Miguel; Hincapié, Carlos A.; Hincapié-Llanos, Gustavo Adolfo; Osorio, Marisol (Frontiers in Insect Science, 2024)
The increasing pressures imposed on ecosystems by the growing needs of the human population are stimulus for research into innovative and unconventional sources of raw materials for different industries. This systematic review was carried out to investigate the available literature on the possible industrial uses of silkworm (Bombyx mori L.) pupae, a residue of silk production. The review was conducted using an adapted version of PRISMA. After a screening process, 105 articles were obtained and subjected to a detailed quantitative and qualitative analysis. It was found that in the last decade there has been a significant increase in the number of papers devoted to the study of the potential use of silkworm pupae in different applications, with a significantly higher number in the last three years of the scope of this review, indicating a growing interest in the subject. From the analysis of the information collected, promising uses in human and animal food, such as fish, mammalian, poultry, swine and companion animals, as well as potential uses for the pharmaceutical industry, were identified. The evaluated research identified compounds with antioxidant activity and important contents of unsaturated fatty acids, which are related to beneficial effects on cardiovascular health, diabetes control, reduction of the risk of developing certain types of cancer and inflammatory activity, among other benefits. One of the most relevant findings is that many studies report a significant concentration of α-linolenic acid in silkworm pupae oil, which is attributed with anticancer, anti-inflammatory, antioxidant, anti-obesity and neuroprotective properties, among others.